Effect of distance-dependent error on the GPS horizontal precision [electronic resource] - Khairul Haswad Hanafi, 1987-, author (2011)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2011